2010
DOI: 10.1103/physrevb.81.140509
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a full energy gap in the nickel pnictide superconductorLaNiAsO1xFxfromA

Abstract: We report systematic 75 As-NQR and 139 La-NMR studies on nickel-pnictide superconductors LaNiAsO1−xFx (x=0, 0.06, 0.10 and 0.12). The spin lattice relaxation rate 1/T1 decreases below Tc with a well-defined coherence peak and follows an exponential decay at low temperatures. This result indicates that the superconducting gap is fully opened, and is strikingly different from that observed in iron-pnictide analogs. In the normal state, 1/T1T is constant in the temperature range Tc ∼4 K≤ T ≤10 K for all compounds… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
17
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 40 publications
1
17
0
Order By: Relevance
“…The low-frequency NQR peak for x = 0.04 gives a smaller θ ∼ 5 K. The increase of θ with increasing x means that the system moves away from the magnetic instability (MI) where θ = 0 K. With further doping, for x = 0.10 and 0.15, no enhancement of 1/T 1 T is seen. Instead, 1/T 1 T decreases with decreasing T , which was recently explained by the loss of the DOS due to a topological change of the Fermi surface [9,25]. The results in previous reports of the lack of the AFSF for x ≥ 0.10 [12,13,15] are consistent with our results for x = 0.10 and 0.15.…”
supporting
confidence: 83%
See 1 more Smart Citation
“…The low-frequency NQR peak for x = 0.04 gives a smaller θ ∼ 5 K. The increase of θ with increasing x means that the system moves away from the magnetic instability (MI) where θ = 0 K. With further doping, for x = 0.10 and 0.15, no enhancement of 1/T 1 T is seen. Instead, 1/T 1 T decreases with decreasing T , which was recently explained by the loss of the DOS due to a topological change of the Fermi surface [9,25]. The results in previous reports of the lack of the AFSF for x ≥ 0.10 [12,13,15] are consistent with our results for x = 0.10 and 0.15.…”
supporting
confidence: 83%
“…Previous nuclear-magnetic resonance (NMR) and nuclear-quadrupole resonance (NQR) measurements have found that the superconductivity is in the spin-singlet state with multiple gaps [4][5][6]. Recent systematic measurements on Ba(Fe 1−x Co x ) 2 As 2 [7], CaFe 2 As 2 under pressure [8], LaNiAsO 1−x F x [9], and BaFe 2 (As 1−x P x ) 2 [10] have suggested that the antiferromagnetic spin fluctuation (AFSF) originated from their multiple electronic bands correlates with the appearance of the pertinent superconducting properties. On the other hand, there are also reports suggesting that AFSF is not important to realize high T c .…”
mentioning
confidence: 99%
“…86. 443 The data show a peak at T c for each sample, called the Hebel-Slichter peak, which is a signature of a conventional s-wave superconducting state. The data follow exponential temperature dependences below T c , indicated as solid curves in the figure, with superconducting energy gaps 2∆ that are close to the BCS value of 3.53 k B T c .…”
mentioning
confidence: 97%
“…5b, where K 0 is T-independent, while the second is due to the band that sinks below the Fermi level 21,22 . Correspondingly, we can write…”
Section: Electrical Resistivity Measurementsmentioning
confidence: 99%